Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1373/jalm.2018.027318
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) for the Identification of Pathogens Causing Sepsis

Abstract: Background Sepsis is a life-threatening condition with high rates of morbidity and mortality; effective and appropriate antibiotic therapy is essential for ensuring patient improvement. To aid in the diagnosis of sepsis, blood cultures are drawn and sent to the microbiology laboratory for pathogen growth, identification, and susceptibility testing. The clinical microbiology laboratory can assist the medical team by providing timely identification of the pathogen(s) causing the bloodstream inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 45 publications
2
34
0
8
Order By: Relevance
“…Our results suggested that narrow spectrum therapy could be advised from day one when a common pathogen with predictable susceptibility profile is identified such as Staphylococcus aureus or Enterococcus faecalis. Early confirmation of contaminated blood cultures was advantageous, leading to potential de-escalation of antibiotics along with complimentary diagnostic testing and shortening of hospital stay, in line with previous studies [2,5,22]. Although, clinical impact on infection control was not noteworthy, there was a case of N. meningitidis bacteremia which helped to early escalation of infection prevention strategies during the first phase of the study.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Our results suggested that narrow spectrum therapy could be advised from day one when a common pathogen with predictable susceptibility profile is identified such as Staphylococcus aureus or Enterococcus faecalis. Early confirmation of contaminated blood cultures was advantageous, leading to potential de-escalation of antibiotics along with complimentary diagnostic testing and shortening of hospital stay, in line with previous studies [2,5,22]. Although, clinical impact on infection control was not noteworthy, there was a case of N. meningitidis bacteremia which helped to early escalation of infection prevention strategies during the first phase of the study.…”
Section: Discussionsupporting
confidence: 65%
“…Sepsis is associated with high mortality [1]; hence rapid identification of bloodstream pathogens and timely clinical decision making are paramount. Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has revolutionized microbiology laboratories with improved workflow for pathogen identification both from solid media and positive blood culture broths [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations